First simultaneous multistation observations of the polar cap thermospheric winds. Issue 1 (11th January 2017) - Wu, Qian; Jee, Geonhwa; Lee, Changsup; Kim, Jeong‐Han; Kim, Yong Ha; Ward, William; Varney, Roger H.
Abstract: Based on two northern (Eureka 80.0°N, 85.9°W, magnetic latitude (MLAT) 88, and Resolute 74.7°N, 94.8°W, MLAT 83) and one southern (Jang Bogo 74.7°S, 164.2°E, MLAT 77) polar cap stations, simultaneous thermospheric wind data during the northern (December) and southern (June) winter months were obtained and compared with the National Center for Atmospheric Research Thermosphere Ionosphere Electrodynamics General Circulation Model (TIEGCM) simulations driven by the Weimer ion convection model. The TIEGCM simulation overestimates the thermospheric wind by 30 to 60%. The thermospheric winds at Eureka were larger than those at Resolute probably because Eureka is at high‐geomagnetic latitude. The observed ion drifts observed by Resolute Incoherent Scatter Radar North face at Resolute also show that the Weimer ion convection model overestimates the ion drift. The observation and simulation also appear to suggest that the ion convection pattern in the Weimer model may be too large. The observed thermospheric winds at Jang Bogo are smaller than the TIEGCM but mostly in the zonal component. The thermospheric winds are smaller at Jang Bogo than the two northern stations which are likely due to their lower magnetic latitude. The results indicate the presence of internal structure in the thermospheric winds inside the polar cap and call for more observations in the polar cap to be undertaken. Key Points: We resolved the question that the Eureka thermospheric winds are larger than those of Resolute The TIEGCM simulation with Weimer ion convection overestimates the thermospheric winds in the polar cap The Weimer ion convection model also overestimates the zonal ion drift at Resolute